Nervous Disorders And Character A Study in Pastoral Psychology and Psychotherapy. - McKENZIE, John G,. (Hoboken : Taylor and Francis, 2013)
First published in 1999.
Cover; Title; Copyright; Preface; Contents; LECTURE 1 Character-Structure and Personality-Disorders; LECTURE 2 Psychology, Psychotherapy and Pastoral Psychology; LECTURE 3 Mental Mechanisms; LECTURE 4 The Nature, Origin and Resolution of Conflicts
Description based upon print version of record.
Keywords: Nervous system -- Diseases; Pastoral psychology; Psychotherapy; RELIGION / Christian Ministry / Pastoral Resources; Electronic books